Gender, power, and violence: responding to sexual and intimate partner violence in society today - Hattery, Angela (Rowman & Littlefield, 2019)
Introduction -- Theory, history, and terminology -- Fraternities -- The military -- Prisons -- Sportsworld -- The Catholic Church -- Hollywood, Washington DC and the #MeToo movement -- Conclusions and a call to action